The Role of Pela Gandong Culture-Based Christian Education Teachers in Shaping Ethical Digital Literacy - Abetsina Lumalessil; Selta Rahangmetan; Agnes Sekerone; Sonia Isabella Tuhumury; Aprelia Hatulely (Harati: Jurnal Pendidikan Kristen, 2026)
This study aims to describe the role of Pela Gandong's culture-based Christian Religious Education teachers in shaping ethical digital literacy in students at SMP Negeri 5 Ambon. This study uses a qualitative approach with a descriptive method. The results of the study show that Christian Religious Education teachers play an important role as educators, role models, guides, and facilitators in instilling Christian values while integrating Pela Gandong cultural values such as brotherhood, mutual respect, solidarity, and social responsibility in the use of digital technology. Through a local culture-based approach, students are guided to not only have technical skills in utilizing digital media, but also to be able to use technology wisely, politely, honestly, and responsibly in accordance with the values of the Christian faith and local wisdom of Maluku. The synergy between teachers, schools, families, and local culture is an important foundation in forming a digital generation that is intelligent, characterful, and able to use technology to strengthen the values of brotherhood and harmonious social life.